Interpreting Conventional Implicature in College Student’s Essays - Rosyiidah, Afiifah Al (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2024)
Abstract Essay can be one of the media to express opinion. This study focuses on analyzing conventional implicatures found in five essays about Madurese local wisdom written by college students. The research adopts a qualitative design. To gather the necessary data, the researcher employs documentary review methods. The collected data are analyzed using an interactive model of data analysis, which encompasses three key steps: data reduction, data display, and data verification/claim. The study reveals that each writer's essay on Madurese local wisdom carries its conventional implicature. The first writer expresses disagreement with certain practices and advocates for awareness and intervention to address the associated negative implications. Another writer highlights Jokotole’s positive attributes and suggests that his behavior can serve as a source of inspiration and guidance in daily life. The preservation and transmission of Madurese folktales are emphasized by another writer, who believes that future generations can develop a better understanding of Madura's cultural identity and heritage through these narratives. Additionally, promoting Madurese culture through the introduction of traditional dances, such as muang sangkal, via live performances, social media platforms, and educational events is proposed by another writer, aiming to familiarize young people with their cultural heritage and nurture a deeper appreciation for their traditions. Lastly, the importance of gathering accurate information, fostering intercultural dialogue, and rectifying misconceptions or incorrect viewpoints is emphasized by the final writer, envisioning the development of a more inclusive and open-minded society that values and respects diverse cultures.